СРАВНИТЕЛЬНЫЙ АНАЛИЗ ТРАДИЦИОННОГО ОБУЧЕНИЯ ПИСЬМУ И ОБУЧЕНИЯ ПИСЬМУ НА ОСНОВЕ АУТЕНТИЧНЫХ МАТЕРИАЛОВ - Уразымбетова, З. (SCIENCE and SOCIETY, 2025)
This article examines the comparative advantages, problems, and consequences of these two approaches, which will allow teachers seeking to improve their pedagogical practice to gain an understanding of them.